2016
DOI: 10.1021/acsami.6b06878
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Thermal-Aging-Induced Degradation of Organometal Triiodide Perovskite on ZnO Nanostructures and Its Effect on Hybrid Photovoltaic Devices

Abstract: Organometal halide perovskite materials are presently some of the pacesetters for light harvesting in hybrid photovoltaic devices because of their excellent inherent electrical and optical properties. However, long-term durability of such perovskite materials remains a major bottleneck for their commercialization especially in countries with hot and humid climatic conditions, thus violating the international standards for photovoltaic technology. Albeit, TiO2 as an electron-transport layer has been well invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…15). 123,124,139 Besides, another reason could be the more basic surfaces of ZnO compared with those of TiO 2 or ITO, which would facilitate protons to transfer and produce methylamine. 124,137 Also, an aqueous solution of ZnI 2 was proposed by Dkhissi et al to probably exist in this degradation.…”
Section: H 2 O At Interfaces Between Perovskite Films and Functional mentioning
confidence: 99%
“…15). 123,124,139 Besides, another reason could be the more basic surfaces of ZnO compared with those of TiO 2 or ITO, which would facilitate protons to transfer and produce methylamine. 124,137 Also, an aqueous solution of ZnI 2 was proposed by Dkhissi et al to probably exist in this degradation.…”
Section: H 2 O At Interfaces Between Perovskite Films and Functional mentioning
confidence: 99%
“…[112] It was observed that the sputtering atmosphere had a crucial effect on the surface properties of the ZnO and, consequently, on the performance of the PSCs. [113] Several works on PSCs with ZnO as an ETM have reported the acute degradation of MAPbI 3 into PbI 2 upon annealing at even low temperatures, [114,115] which raises concerns about the suitability of ZnO in real world applications. [113] Several works on PSCs with ZnO as an ETM have reported the acute degradation of MAPbI 3 into PbI 2 upon annealing at even low temperatures, [114,115] which raises concerns about the suitability of ZnO in real world applications.…”
Section: Znomentioning
confidence: 99%
“…2 Besides TiO 2 , ZnO may also react with perovskite under illumination and exacerbate the decomposition of the perovskite deposited on it [112] . A. Dhar et al [113] reported that the presence of ZnO accelerated the degradation rate of MAPbI 3 films under ambient annealing. Due to the relative basic nature of ZnO surface, proton-transfer reactions may happen at the ZnO/CH 3 NH 3 PbI 3 interface, leading to the de-protonation of the methylammonium cation.…”
Section: Effect Of Interface Reactionmentioning
confidence: 99%